Analisis Penerapan Etos Kerja Islami pada Karyawan Industri Rumahan Terasi Kecamatan Kaliwates Jember - Citra Dwi Aulia; Ervin Fitria Faradila; Vira Vionika; Aniqotuzzuhro' Fitriana (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2023)
This article aims to find out the application of the Islamic work ethic to employees of the shrimp paste home industry. This research uses qualitative research techniques with descriptive research types. Data collection methods used are interviews, observation and documentation. Data analysis in this study used triangulation techniques. The results of this study indicate that the shrimp paste home industry employees apply the Islamic work ethic by adopting an attitude of sincerity, honesty, consistency, courage to take consequences, and responsibility. The Islamic work ethic applied by employees has an impact on increasing employee performance and customer satisfaction for the services of these employees and a good work ethic will also produce good performance which will certainly have a significant effect on the progress of the industry.